Role of Forgiveness in The Grief Process for Children in Crisis - Gaskin, Judy Ann (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Children are a group of people who often experience trauma, which then leads to a cycle of cycle. Various psychological help has been sought but has not addressed spiritual recovery. This study discusses forgiveness in the process of children who are in crisis so that spiritual development occurs in children. The author uses various library sources and analyzes the biblical text in discussing the topic. This study uses hermeneutical approaches to promoting biblical texts as applicable to everyday life. Forgiveness plays an essential role in the recovery process. Children need help identifying what they are grateful for regarding the forgiveness process. Gratitude produces liberation and leads to hope, thus leading to change thatresults in spiritual healing. To help children forgive, children need reconciliation with the creator. To meet this need, spiritual directors play an important role in assisting children to meet their spiritual needs. Spiritual directors can help traumatized children replace their distorted view of themselves, others, and God with a proper view of the truth. This study aims to involve the contribution of existing practical theology to propose the idea of the role of forgiveness in the grieving process for children experiencing a crisis.